Simulation and data analysis of the structural and compositional characteristics of perovskite at the nanoscale under air and vacuum conditions - Ng, Shirley (Nanyang Technological University, 2022)
TEM-based characterizations have emerged as a critical characterisation tool for better understanding perovskite materials and devices. However, when organic-inorganic hybrid perovskites (OIHPs), MAPbI3, are exposed to the electron beam and ambient conditions during TEM acquisition, the material degrades quickly and is damaged by the beam. As a result, it is necessary to comprehend the optimal environmental TEM conditions to limit electron beam damage and degradation. Here, we performed TEM characterizations on MAPbI3 exposed in two distinct environments: air and vacuum, with increasing total electron dose. The data simulations and analysis of SAED patterns indicate that under air exposure, the SAED peaks of MAPbI3 saw a rapid decay of intensity and new peaks formed at a higher total electron dose of ~986.4 E-01 / Å^2. This may be caused by the drastic degradation of the MAPbI3 induced by the electron beam leading to the formation of intermediate phases and PbI2. On the other hand, when exposed to vacuum, the intensity of SAED peaks reduced at a slower rate and no new peaks were formed, revealing only minor degradation of MAPbI3 at a high total electron dose of ~2466 E-01 / Å^2.